Antimicrobial evaluation of spirooxindolopyrrolidine engrafted indoles against multidrug resistant ESKAPE clinical pathogens - Natarajan Arumugam; Khloud Ibrahim Al-Shemaimari; Mohammad Altaf; Karuppiah Ponmurugan; Dhanaraj Premnath; Sinouvassane Djearamane; Ling Shing Wong; Saminathan Kayarohanam (Journal of King Saud University: Science, 2024)
The synthesis of a new class of effective antibiotics and antimicrobial agents with less toxicity is highly desirable due to bacterial resistance to antibiotics has increased dramatically. In this context, molecules that embedding a spiro moiety are attractive from a medicinal chemistry point of view as these spiro heterocycles show a vital part in the development of delivery systems for antimicrobial therapies. In the present study, the synthesis and antimicrobial evaluation of structurally attractive complex hybrid heterocycles comprising spriooxindolopyrrolidine and indole heterocycles was attained in quantitative yields by cycloaddition strategy. The new class of spirocompouds were unequivocally assigned through spectroscopic analysis and the antimicrobial efficacy were assessed against six microbial pathogens. Among them, compound 4a, bearing chlorine substituted derivative showed significant activity against tested ESKAPE pathogens. The maximum zone of inhibition observed against ESKAPE microbial pathogens causing infectious disease ranged from 6.75 ± 0.40 to 19.75 ± 1.15 mm, with MIC values ranging between 16.00 to  > 256.00 µg/ml .